Weight gain, metabolic disturbances, and physical health care in a Brazilian sample of outpatients with schizophrenia - Gordon PC (Dove Medical Press, 2013)
Pedro Caldana Gordon,1,2 Josefa Cynara Xavier,2 Mario Rodrigues Louzã21Department of Psychiatry, Faculdade de Medicina, Universidade de São Paulo, Brazil; 2Schizophrenia Research Program, Institute of Psychiatry, Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo, BrazilBackground: In the last few decades, a large number of studies have produced compelling evidence that patients with schizophrenia are at increased risk for developing several medical conditions and diseases, including obesity, metabolic disturbances, and cardiovascular diseases. Several protocols have been designed with the aim of reducing such risk.Objective: To investigate current physical health status in a population of outpatients with schizophrenia.Methods: A cross-sectional study was conducted in our outpatient clinic, selecting subjects who met DSM-IV diagnosis criteria for schizophrenia. Data were collected regarding clinical characteristics, lifestyle, medication in use, and biometric and laboratory parameters.Results: A total of 261 patients were included. We found a high prevalence of elevated body mass index (BMI > 25) (70%), dyslipidemia (73.2%), and metabolic syndrome (28.7%). Patients' ages were associated with worsened lipid profiles, but other variables, such as disorder duration or type of antipsychotic in use, were not associated with any metabolic disturbance. Despite the increased prevalence of these conditions, only a small portion of the sample was under regular medical treatment.Conclusion: Outpatients with schizophrenia show signs of poor physical health conditions. These findings reinforce the need for an intensive and appropriate approach to assure that these patients receive adequate clinical referral and treatment.Keywords: psychosis, obesity, public health, antipsychotic drugs, cardiovascular disorders